Empowering Rural Youth: Socialization of Higher Education Scholarships for the Karang Taruna Youth Organization in Dusun Kampir - Nurmasitah, Sita; Kafabina, Indaha Nawaya; Anjani, Zahrattun Nissa Rahma; Astutik, Indriati Ayu; Widiyanto, Yosep April (Universitas Negeri Semarang, 2025)
Higher education plays an important role as a foundation in developing quality human resources who are able to compete in the global era. However, in many rural areas, access to and understanding of the importance of higher education is still limited due to factors such as low parental education, high costs, and a lack of information about scholarships. The community service program implemented by UNNES GIAT 12 in Kampir Hamlet, Plososari Village, Kendal, aims to address these challenges by providing comprehensive scholarship information to local youth. The objectives of this program include increasing knowledge about various types of scholarships, particularly distinguishing between KIP Kuliah and merit-based scholarships, as well as guiding participants on how to access scholarship information. Using educational and interactive methods, this intervention measured the knowledge of 10 participants through pre-tests and post-tests. The results showed a significant increase in understanding, with the average pre-test score of 1.32 increasing to 3.6 on the post-test. This remarkable increase confirms the effectiveness of targeted scholarship outreach in bridging the information gap and motivating rural youth to pursue higher education. Thus, this program contributes to increased educational participation and human capital development in underserved areas.